2021
DOI: 10.3390/ijerph18115617
|View full text |Cite
|
Sign up to set email alerts
|

Noise Disturbance and Potential Hearing Loss Due to Exposure of Dental Equipment in Flemish Dentists

Abstract: Long-term exposure to occupational noise is often associated with noise-induced hearing loss (NIHL) among dentists. This study aims to investigate potential hearing loss (HL) and self-reported annoyance as a result of exposure to noise produced by contemporary dental equipment. Methods: Three cohorts participated: 53 dentists with more than 5 years of service, 47 dentists with at most 5 years of service, and 53 pharmacists as controls, age and gender-matched to the first group. After the exclusion of one perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
(81 reference statements)
0
12
0
1
Order By: Relevance
“…Las investigaciones entono a la pérdida de audición inducida por exposición a ruido son controversiales. Si bien, algunos autores han encontrado una correlación directa entre la pérdida de la audición y la exposición a ruido tanto en los profesionales como en estudiantes de odontología [19,20], otros estudios no han identificado diferencias en la pérdida de la capacidad auditiva entre odontólogos y otros profesionales del área de la salud [ 21]. Más recientemente, una revisión sistemática ha concluido que los profesionales de la salud bucal están expuestos a ruidos excesivos en una jornada laboral de ocho horas, dado que los niveles de ruido de los dispositivos dentales pueden acumularse y por tanto esto podría aumentar el riesgo de pérdida auditiva [22].…”
Section: Discussionunclassified
“…Las investigaciones entono a la pérdida de audición inducida por exposición a ruido son controversiales. Si bien, algunos autores han encontrado una correlación directa entre la pérdida de la audición y la exposición a ruido tanto en los profesionales como en estudiantes de odontología [19,20], otros estudios no han identificado diferencias en la pérdida de la capacidad auditiva entre odontólogos y otros profesionales del área de la salud [ 21]. Más recientemente, una revisión sistemática ha concluido que los profesionales de la salud bucal están expuestos a ruidos excesivos en una jornada laboral de ocho horas, dado que los niveles de ruido de los dispositivos dentales pueden acumularse y por tanto esto podría aumentar el riesgo de pérdida auditiva [22].…”
Section: Discussionunclassified
“…The researcher also suggested the application of protective strategies in dental clinics. 84 out of 304 tested ears (28%) showed a pattern of hearing loss, the audiometric analysis showed that 30 ears had a pattern indicating another pattern of hearing loss, influenced mainly by age (Dierickx et al, 2021). But this statement has no meaning in statistics.…”
Section: Introductionmentioning
confidence: 92%
“…Dental professionals, in general, are predisposed to a variety of occupational hazards purely by the nature of their occupation. From life-threatening infections such as Viral Hepatitis and HIV to the use of chemical-based materials, radiation, and last but not least, noise [1][2][3][4][5]. Previous studies have shown that Hearing loss may not be symptomatic, but some dentists have previously reported signs such as Tinnitus [6].…”
Section: Introductionmentioning
confidence: 99%